Fenomena Remaja Menggunakan Media Sosial dalam Membentuk Identitas - Primada Qurrota Ayun (Universitas Ahmad Dahlan, 2015)
The Internet and teens are the two things are interrelated. Survey from the Ministry of Communications and Information in Indonesia showed that the largest internet usage is to access social media. In Indonesia, the phenomenon of young people in using social media is quite interesting to study. Teens build their self-identity to obtain the image they want and express private problem into a social media issues raised in this study. The theory used in this research is the Social Identity Theory, Symbolic Interaction and Media Ecology. This study is a qualitative study using phenomenological method. Results from this study showed that adolescents show identity vary in their social media and they express personal problems in social media, but in the form implied.Keywords: Social Media, Teens, Identity.